The effectiveness of cooperation of industrial enterprises - Ginevičius, Romualdas (Journal of Business Economics and Management, 2010)
Cooperation is a strategy of an enterprise, seeking to retain its market share. The cooperation means the establishment of long‐term relations of production between economically and legally independent enterprises. The measurement of the level of cooperation achieved plays an important part in this process because it helps to determine the effect of cooperation on the efficiency of commercial activities of an enterprise, as well as the extent of cooperation influence, the conditions required for effective cooperation of enterprises, etc. In the present investigation, the analysis of the cooperation influence on the competitiveness of an enterprise is made, based on the suggested formula for determining the level of the cooperation achieved by enterprises. The analysis performed shows that this influence is not strong, implying that the appropriate organisational forms of cooperation have not been found yet. Cooperation mainly affects the profitability of an enterprise. The analysis of cooperation in the area of production shows that cooperation in production, and the development of new technologies and new products is most important for achieving enterprise profitability. The number of partners also has a great influence on cooperation effectiveness.Gamybos įmonių kooperacijos efektyvumas Santrauka. Kooperacija  yra  vienas  iš  įmonės  strateginės  elgsenos  būdų  siekiant  išlikti  rinkoje. Tai  nuolatinių  ilgalaikių gamybinių  ryšių  nustatymas  tarp  ūkiškai  ir  teisiškai  savarankiškų  įmonių.  Svarbus  vaidmuo kooperacijoje tenka jos pasiekto lygio matavimui, nes be to neįmanoma nagrinėti jos poveikio įmonių komercinės veiklos efektyvumui, nustatyti šio poveikio ribų, efektyvios kooperacijos sąlygų ir pan. Remiantis pasiūlyta įmonių kooperacijos pasiekto lygio nustatymo formule, atlikta kooperacijos poveikio įmonės konkurencinės veiklos rezultatams analizė parodė, kad jis nėra stiprus, vadinasi, dar nerastos tinkamos organizacinės jos formos. Kooperacija daro didžiausią įtaką įmonės turto pelningumui. Gamybos funkcijų kooperavimo analizė parodė, kad labiausiai įmonių turto pelningumą veikia gamybos bei  naujų  technologijų  ir  produkto  išvystymo  kooperavimas.  Didelę  įtaką  kooperacijos  efektyvumui taip pat turi partnerių skaičius.Reikšminiai  žodžiai: įmonės  kooperacija,  kooperacijos  matavimas,  kooperacijos  poveikis  įmonės komercinės veiklos rezultatams.First Published Online: 09 Jun 2011